Magical Realism and Kafkas Construction of Identity in Haruki Murakamis Kafka on the Shore - FAHMI APRILIYANTI AMIRULLAH (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
Magical realism has become remarkable genre in literary works. One of many novelists who apply magical realism in his work is Haruki Murakami, in one of his works entitled Kafka on the Shore. This novel tells about a story of Kafka and Nakata whom their journey is corresponding to each other. For that reason, this study will reveals how magical realism is depicted in Kafka on the Shore by using magical realism characteristics proposed by Wendy Faris; Irreducible Element, Phenomenal World, Unsettling Doubts, Merging Realm and Disruption of Time, Space and Identity. In addition, to reveals how Kafka constructing his identity upon the disruption he got by using Lacanian Hero as the aim of and symbolical order as the media of the construction of identity. The analysis shows that magical realism depicted in the novel by the presence of the events that indicated as magical realism characteristics. Other than that, by using Lacanian concept of Hero and Symbolical order, the finding reveals how Kafka construct his identity by being hero for himself, means that he needs to accept his fate, not runs to the world of compensation and to pays the price for his actions while he tries to accept the fate he has.Keywords: Magical Realism, Identity, Construction, Lacanian Hero, Symbolical Order.